Pengaruh Fungi Mikoriza Arbuskula Indigen Terhadap Kerapatan Gulma, Pertumbuhan dan Produksi Jagung Manis (Zea mays Saccharata (Sturt.) Bailey) - Halim Halim; Makmur J. Arma; Fransiscus S. Rembon; Resman Resman (Jurusan Biologi FMIPA Universitas Cenderawasih, 2020)
This study aims to determine the effect of local arbuscular mycorrhizal fungi (AMF) on weed density, growth and yield of sweet corn in marginal soils. This study used a randomized block design with local AMF propagules which consisted of 4 levels: 0 g/planting hole or control (A0), 15 g/planting hole (A1), 30 g/planting hole (A2) and 45 g/planting hole (A3). The research parameters observed were: weed density, plant height, stem diameter, crop yield, and the percentage of AMF infection in the roots of corn plants. The results showed that the highest weed dominance value at the age of 14 DAP was Cyperus rotundus as 36.8% in treatment of AMF 45 g/planting hole (A3), age 56 DAP the highest weed dominance value was Hyptis capitata as 47.1% in the treatment of AMF 30 g/planting hole. The best plant height and stem diameter were found in the treatment of AMF 45 g/planting holes (A3) at 56 DAP, the average plant height reached 234.05 cm and the average stem diameter reached 3.72 cm. Increased production of corn plants that were given local AMF ranged from 2.70 to 3.10 tons ha-1 or an average increase in overall corn crop production of 2.86 tons ha-1. The average percentage of mycorrhiza fungi infections in the highest roots of corn plants in the treatment of AMF 45 g/planting hole (A3) as 94%. Key words: Arbuscular mycorrhiza fungi; vesicles; hypha; maize; ultisols